LIGA fabrication of nanocrystalline Ni–W alloy micro specimens from ammonia-citrate bath - Haseeb, A.S. Md. Abdul; Bade, Klaus (Springer Verlag (Germany), 2008)
Ammonia-citrate bath has been investigated for the deposition of nano crystalline Ni - W alloy micro components using the LIGA process. First the bath stability and deposit characteristics were studied. Fabrication of micro specimens were then carried out on silicon substrates covered with novolac as well as thick PMMA resist for LIGA. Effects of different parameters like current density, nickel ion and tungsten ion concentration in the bath, deposition time etc. on the deposit characteristics and current efficiency were studied. The deposited Ni - W samples were characterized by scanning electron microscopy, energy depressive X-ray spectroscopy, light optical microscopy and X-ray diffraction. Results show that during a few tens of hours of deposition, ammonia loss from the covered bath used is minimal and the bath remains stable. Selection of proper bath and deposition parameters allows a window for the deposition of crack free, thick, nano crystalline nickel-tungsten alloys. Using the optimum parameters, it has been possible to fabricate Ni-12 at W micro tensile specimens with a nominal thickness of 120 mu m by the LIGA process.